Proteasomal inhibition after injury prevents fibrosis by modulating TGF-β1 signalling. Issue 2 (15th September 2011) - Mutlu, Gökhan M; Budinger, G R Scott; Wu, Minghua; Lam, Anna P; Zirk, Aaron; Rivera, Stephanie; Urich, Daniela; Chiarella, Sergio E; Go, Leonard H T; Ghosh, Asish K; Selman, Moises; Pardo, Annie; et al.
Abstract : Background: The development of organ fibrosis after injury requires activation of transforming growth factor β1 which regulates the transcription of profibrotic genes. The systemic administration of a proteasomal inhibitor has been reported to prevent the development of fibrosis in the liver, kidney and bone marrow. It is hypothesised that proteasomal inhibition would prevent lung and skin fibrosis after injury by inhibiting TGF-β1 -mediated transcription. Methods: Bortezomib, a small molecule proteasome inhibitor in widespread clinical use, was administered to mice beginning 7 days after the intratracheal or intradermal administration of bleomycin and lung and skin fibrosis was measured after 21 or 40 days, respectively. To examine the mechanism of this protection, bortezomib was administered to primary normal lung fibroblasts and primary lung and skin fibroblasts obtained from patients with idiopathic pulmonary fibrosis and scleroderma, respectively. Results: Bortezomib promoted normal repair and prevented lung and skin fibrosis when administered beginning 7 days after the initiation of bleomycin. In primary human lung fibroblasts from normal individuals and patients with idiopathic pulmonary fibrosis and in skin fibroblasts from a patient with scleroderma, bortezomib inhibited TGF-β1 -mediated target gene expression by inhibiting transcription induced by activated Smads. An increase in the abundance and activity of the nuclear hormone receptor PPARγ, a repressor of Smad-mediated transcription, contributed to this response. Conclusions: Proteasomal inhibition prevents lung and skin fibrosis after injury in part by increasing the abundance and activity of PPARγ. Proteasomal inhibition may offer a novel therapeutic alternative in patients with dysregulated tissue repair and fibrosis.